Fuel-oxidizer mixtures: a lab and field study. Issue 2 (2nd April 2020) - Rettinger, Ryan C.; Porter, Matthew; Canaria, Jeffrey; Smith, James L.; Oxley, Jimmie C.
ABSTRACT: Improvised explosive may be as primitive as a fuel and oxidizer mixture; yet not all fuel-oxidizer mixtures are explosive. Predicting explosive potential from laboratory-scale tests is desirable to screen a large matrix of potential threats in varying concentrations. Herein the properties of various fuel/oxidizer mixtures were measured at small scale (2 g) with bomb calorimetry and on large scale (5 kg) with high speed photography for detonation velocity and with piezoelectric pressure probes for TNT air blast equivalence. Potassium nitrate (KN), potassium chlorate (KC), potassium permanganate (KMnO4 ), potassium iodate (KIO3 ), ammonium nitrate (AN), and ammonium perchlorate (AP) were prepared with sucrose (Su) and aluminum (Al) fuel. Results were compared to each other as well as predictions from Cheetah thermochemical code.